2021: A year of transition for social security and welfare policies in Italy?. Issue 2 (3rd April 2022) - Pavolini, Emmanuele; Saraceno, Chiara
ABSTRACT: The key question addressed by this article is whether the pandemic might represent one of those 'critical conjunctures' capable of altering the direction of development of the Italian welfare state. Having reviewed the main explanations found in the literature for the difficulties in modernizing the Italian welfare state, we provide an answer by analysing what happened in 2021 in three policy areas: that concerning families with children, and early childhood education and care (ECEC); that concerning the support of dependent old people, and that concerning minimum income policies, looking at the role played by party competition as well as by civil society. We find that while in the field of family policy and ECEC there has been a clear shift towards greater investment, in the area of care for dependent old people, developments have been more hesitant and more ambivalent. With regard to minimum income provision, political conflict has for the time being impeded any attempt at reform. The answer to the research question therefore is only partially positive